Fostering openness in open science: An ethical discussion of risks and benefits - Khalil, Ali Talha; Shinwari, Zabta Khan; Islam, Arshad (Frontiers in Political Science, 2022)
Transformation of science by embracing the concepts of open science presents a very attractive strategy to enhance the reliability in science. Open science policies embody the concepts of open data and open access that encompasses sharing of resources, dissemination of ideas and synergizing the collaborative forums of research. Despite of the opportunities in openness, however, there are grave ethical concerns too and presents a dual-use dilemma. Access to the sensitive information is seen as a security risk, and also possesses other concerns like confidentiality, privacy, affordability etc. There are arguments regarding open science can be harmful to marginalized groups. Through this paper, we aim to discuss the opportunities of open science as well as the ethical and security aspects which requires further deliberation before full-fledged acceptance in the science community.